Analisis Pengembangan Kawasan Kota Baru Pattallassang - Andika Saputra Hasanuddin; Rahmawati Rahman; Emil Salim Rasyidi (Fakultas Teknik Universitas Bosowa, 2022)
This study aims to determine the level of power support and capacity of the settlements of the new city of Pattallassang and to know the direction of space control in terms of carrying capacity and carrying capacity to accommodate settlements. This type of research is mixed methods research. Study This is a research step by combining two previous forms of research, namely qualitative research and quantitative research. using carrying capacity and power analysis tools to accommodate settlements. The main conclusion of this study is that the district pattallassang can still accommodate residents to live. The results of the analysis show the area with the highest carrying capacity to be developed into a residential area is the village Paccellekang with a DDP value of 30.35 or > 1, followed by village Panaikang of 30.35 then borongpalala town of 25.25 and the lowest carrying capacity value is in the village of Sunggumanai with the importance of 11.95 and timbuseng town of 5.80. And Based on the analysis of the results conducted by the author shows that Pattallassang still able to accommodate 397,423 residents, as for the villages that can adapt and support settlements the highest is in the village of paccellekang with a population that is can accommodate 101,840 people and the town of jenemadinging with the lowest result is 28,683 people.